Control of quantum electrodynamical processes by shaping electron wavepackets - Liang Jie Wong (Nature Portfolio, 2021)
Here the authors show that radiation emitted by individual electrons can be controlled by shaping the electron wavepacket. They present feasible examples for applications including collimated and monochromatic X-ray emission from specially shaped electrons.